2020
DOI: 10.5946/ce.2019.073
|View full text |Cite
|
Sign up to set email alerts
|

Experience of the Endoscopists Matters in Endoscopic Retrograde Cholangiopancreatography in Billroth II Gastrectomy Patients

Abstract: Background/Aims: Altered anatomy is a challenge in endoscopic retrograde cholangiopancreatography (ERCP) for patients with Billroth II anastomosis. In this study, we investigated the overall success and role of endoscopist experience. Methods: Data of patients who underwent ERCP between 2014 and 2018 after a previous Billroth II operation were retrieved retrospectively from 2 tertiary ERCP centers. The procedures were performed by 2 endoscopists with different levels of experience. Clinical success was defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…In another study which evaluated the experience of endoscopists in ERCP procedure in 75 Billroth II gastrectomy patients, ERCP success rate of an inexperienced endoscopist was found to be lower, but was not statistically significant. In the same study, perforation rate of the afferent loop for inexperienced endoscopist was higher than the experienced endoscopist (6.25% vs 0%) [10]. In our study, ERCP procedures were performed by a single experienced endoscopist in a single high-volume center.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In another study which evaluated the experience of endoscopists in ERCP procedure in 75 Billroth II gastrectomy patients, ERCP success rate of an inexperienced endoscopist was found to be lower, but was not statistically significant. In the same study, perforation rate of the afferent loop for inexperienced endoscopist was higher than the experienced endoscopist (6.25% vs 0%) [10]. In our study, ERCP procedures were performed by a single experienced endoscopist in a single high-volume center.…”
Section: Discussionmentioning
confidence: 52%
“…Clinical success rate of ERCP in patients with Billroth II gastrectomy have ranged from 62.5-91.7% with the sideviewing duodenoscope compared to 62.5-91.3% with the forward-viewing endoscope [1,2,4,10,11]. In our study, the desired clinical goal was achieved in 68.3% and 79.4% of patients, respectively.…”
Section: Discussionmentioning
confidence: 55%
“…The relative difficulty of ERCP procedures may vary depending on patient characteristics, biliary anatomy, procedural indication, and intervention. 7 , 13 According to one grading system, ERCP procedures for small-to-medium sized biliary stones are less difficult to identify than extrahepatic strictures. 7 , 14 This is congruent with the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The postprocedural follow-up period was 7 d in both the groups. Choi et al [ 32 ] reported a higher technical success rate in the PTBD group than in the EUS-BD group, although the functional success rate was comparable between the two groups[ 35 ].…”
Section: Discussionmentioning
confidence: 99%